2007
DOI: 10.1038/nm1563
|View full text |Cite
|
Sign up to set email alerts
|

Reverse signaling through GITR ligand enables dexamethasone to activate IDO in allergy

Abstract: Glucocorticoid-induced tumor necrosis factor receptor (GITR) on T cells and its natural ligand, GITRL, on accessory cells contribute to the control of immune homeostasis. Here we show that reverse signaling through GITRL after engagement by soluble GITR initiates the immunoregulatory pathway of tryptophan catabolism in mouse plasmacytoid dendritic cells, by means of noncanonical NF-kappaB-dependent induction of indoleamine 2,3-dioxygenase (IDO). The synthetic glucocorticoid dexamethasone administered in vivo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
334
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 294 publications
(345 citation statements)
references
References 50 publications
10
334
1
Order By: Relevance
“…IDO1 expression is contingent on the noncanonical pathway of NF-kB activation 19,26,27 . Molecular dissection of NF-kB activation has shown that NF-kB can be induced by the socalled canonical (classical; IkB kinase (IKK)b-dependent) and noncanonical (alternative; IKKa-dependent) signalling pathways, leading to distinct patterns in the individual NF-kB subunits that are activated and the downstream genetic responses that are induced.…”
Section: Resultsmentioning
confidence: 99%
“…IDO1 expression is contingent on the noncanonical pathway of NF-kB activation 19,26,27 . Molecular dissection of NF-kB activation has shown that NF-kB can be induced by the socalled canonical (classical; IkB kinase (IKK)b-dependent) and noncanonical (alternative; IKKa-dependent) signalling pathways, leading to distinct patterns in the individual NF-kB subunits that are activated and the downstream genetic responses that are induced.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the ITIM‐mediated IDO1 plasticity would translate in DCs into opposite functional phenotypes, that is , immunoadjuvant versus immunoregulatory in nature 9. In this regard, it should be noted that pDCs represent the most flexible DC subset, capable of rapidly shifting from an immunostimulatory to an immunosuppressive programme and vice versa in response to inflammatory versus anti‐inflammatory signals 25, 37. The inflammatory versus anti‐inflammatory milieu sensed by pDC may promote not only a differential expression of the IDO1's molecular partner ( i.e .…”
Section: Discussionmentioning
confidence: 99%
“…All purification procedures of splenic Ido1 −/− pDCs and CD8 − DCs (hereafter referred to as cDCs, for conventional DCs) were as described 7, 8, 22, 23, 24, 25. Plasmid constructs coding for WT or IDO1 mutants (Y115E, Y253E and Y115_253E, in which either one or both phosphorylable tyrosines were replaced by a glutamate residue) were used as templates for in vitro transcription of mRNA, using the mMESSAGE mMACHINE T7 Ultra Kit (Ambion, Waltham, MA USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to the situation in AA: These individuals do have considerable specific blood IgE levels against common aeroallergens (51), although the IDO pathway seems to be active during allergen exposure. In a mouse model, it has recently been shown how IDO can mediate a glucocorticoid-dependent anti-inflammatory effect in allergic bronchopulmonary aspergillosis (ABPA) (52). Engagement of the glucocorticoid-induced tumor necrosis factor receptor ligand (GITRL) on pDCs by soluble GITR has been found to initiate trp catabolism by inducing IDO in pDCs.…”
Section: Ido and The Ido Pathway Control Allergic Inflammationmentioning
confidence: 99%